Neutrophil-to-Lymphocyte Ratio as a Prognostic Biomarker for Patients With Metastatic Renal Cell Carcinoma Treated With Immune Checkpoint Inhibitors: A Systematic Review and Meta-Analysis - Chen, Xiuqiong; Meng, Fanqiao; Jiang, Richeng (Frontiers in Oncology, 2021)
Background and aim: Increasing evidence suggested that NLR is related to the prognosis of RCC patients treated with ICIs. However, these findings were inconsistent. We performed this analysis to explore the utility of NLR in RCC patients treated ICIs. Methods: A comprehensive search of PubMed, Web of Science, EMBASE were performed for studies evaluating the prognostic value of NLR. OS and PFS were the clinical outcomes. All statistical analysis was performed in Stata 12.0 software. The pooled HRs and 95% CIs of NLR for OS and PFS were calculated with random-effect models. Heterogeneity was evaluated on the basis of Cochran's Q test and I2 value. Egger's and Begg’s tests were applied to assess publication bias precisely. Sensitivity analysis was carried out by trim and fill method to test whether the results were stable. Results: Twelve studies encompassing 1275 patients were included in final analysis. Our results showed high NLR of baseline or pretherapy was associated with poor OS (HR: 2.23, 95% CI: 1.84-2.70; P<0.001) and PFS (HR: 1.78, 95% CI: 1.72-2.09, P<0.001). During the course of treatment, a decrease in NLR was associated with a significantly longer OS (HR, 0.34; 95% CI, 0.20–0.56; P<0.001) and PFS (HR: 1.78, 95% CI: 1.72-2.09, P<0.001) compared to an increase in NLR. There was no significant publication bias and heterogeneity in our study. Conclusion: Elevated NLR was associated with an adverse OS and PFS in RCC patients treated with immune checkpoint inhabitors. NLR could be as a readily available prognostic biomarker for these patients. Further investigation still needs to be made to validate our results.